ANALISIS RASIO KEUANGAN PEMERINTAH DAERAH KOTA SURABAYA SEBAGAI TOLOK UKUR GOOD GOVERNMENT - Clemment Marvello Fedihartono; Tri Andjarwati (Jurnal Nirta : Inovasi Multidisiplin, 2024)
Surabaya City is one of the cities with high population growth. This population increase certainly has consequences for the provision of adequate public facilities and employment opportunities that ensure the survival and welfare of the population. One way to assess performance based on the principles of Good Government is through the financial health of the Local Government organization. The purpose of this study based on the formulation of the problems described above is to determine the results of the Financial Ratio Analysis of the Surabaya City Local Government as a Good Government Benchmark. This research uses a quantitative descriptive method, with secondary data coming from the official website of the Information and Data Management Officer. The results of this study indicate that in the 2019-2023 fiscal year the Surabaya City Government in managing its Regional Finances is classified as Inefficient. However, the Surabaya City Government in using resources to obtain PAD is classified as Highly Effective. In terms of regional autonomy, Surabaya City is classified in the Delegative category. However, in terms of allocating resources, the Surabaya City Government still allocates too much to the process of governance compared to the acquisition of long-term assets / fixed assets. In this fiscal year, Surabaya City did not always experience good financial growth, but there were still fiscal years where Surabaya City experienced a decrease in the Realization of Regional Original Revenue and Realization of Regional Expenditure.